Pathological Roles of Neutrophil-Mediated Inflammation in Asthma and Its Potential for Therapy as a Target - Han Gao; Songmin Ying; Yuanrong Dai (Journal of Immunology Research)
Asthma is a chronic inflammatory disease that undermines the airways. It is caused by dysfunction of various types of cells, as well as cellular components, and is characterized by recruitment of inflammatory cells, bronchial hyperreactivity, mucus production, and airway remodelling and narrowing. It has commonly been considered that airway inflammation is caused by the Th2 immune response, or eosinophilia, which is a hallmark of bronchial asthma pathogenesis. Some patients display a neutrophil-dominant presentation and are characterized with low (or even absent) Th2 cytokines. In recent years, increasing evidence has also suggested that neutrophils play a key role in the development of certain subtypes of asthma. This review discusses neutrophils in asthma and potentially related targeted therapies.